Evaluation of knowledge and attitudes of dentists and dental students about oral cancer - Dicle Altındal; Filiz Acun Kaya (Current Research in Dental Sciences)
Objective: This study aimed to evaluate the knowledge and negative attitudes of dentists and 4th-grade and 5th-grade students of dentistry towards oral cancer (OC). Methods: The study was conducted on 417 individuals consisting of 100 dentists, 186 5th-grade, and 131 4th-grade students. The questionnaire included questions on demographic characteristics, 10 questions measuring their knowledge about OC risk factors (knowledge-risk factors), 5 questions measuring their knowledge regarding the diagnosis of OC (knowledge-diagnostic procedures), and 11 questions assessing their attitudes towards OC (negative attitudes). Results: While there is no significant difference between dentists and 5th-grade students in knowledge-risk factors and knowledge-diagnostic procedures total scores, the total score of the 4th-grade students was statistically significantly different from these groups (P =.001). Looking at the negative attitudes total score, there is no significant difference between 5th and 4th-grade students, while total score of dentists was observed a statistically significant difference (P=.001). While knowledge-risk factors and knowledge-diagnostic procedures total scores were significantly and positively correlated (r=.287, P<.05), negative attitudes total score showed a significant negative correlation with knowledge-risk factors total score (r=.103, P<.05). Deficiencies were observed regarding the clinical characteristics of the prior oral lesion among participants. The group who considered leukoplakia and erythroplakia most likely to become precancerous lesions were 5th-grade students by 81.7%. Most participants indicated their need for further training, especially on OC and screening.Conclusion: In the study, deficiencies were observed in the groups about OC. Therefore, deficiencies should be assessed comprehensively at regional and national levels, and it should be addressed.Keywords: Dental student, dentists, knowledge, mouth neoplasms, risk factors, squamous cell carcinoma